2020
DOI: 10.1080/1547691x.2020.1755397
|View full text |Cite
|
Sign up to set email alerts
|

Circulating inflammatory markers in cervical cancer patients and healthy controls

Abstract: There is increasing evidence that host inflammatory responses play an important role in the development and progression of cancers. There are some data that cancer is associated not only with inflammation at the site of the lesion, but also with dysregulations of the host overall systemic immune response. In the case of cervical cancer, inflammation is an important factor associated with the development, progression, and potential metastasis of the disease. What is unclear still in the potential for modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
2
11
1
Order By: Relevance
“…The presence of inflammatory factors maintains and promotes tumor progression (18). The level of serum IFNb, IL-1b, and IL-6 was significantly higher in HPV-positive patients compared to healthy controls (19). Higher level of IL-10 and TNFa was also observed in HPV-positive women with different types of cervical lesions (20).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of inflammatory factors maintains and promotes tumor progression (18). The level of serum IFNb, IL-1b, and IL-6 was significantly higher in HPV-positive patients compared to healthy controls (19). Higher level of IL-10 and TNFa was also observed in HPV-positive women with different types of cervical lesions (20).…”
Section: Discussionmentioning
confidence: 99%
“…Production of CRP in the liver is strongly induced by pro-in ammatory cytokines such as IL-6 19,41 . Hence, CRP could have a crucial role in the presence of systemic in ammatory response in NSCLC could be associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic in ammation has been recognized as a key factor that contributes to the development and progression of a variety of malignancies 17 . Elevated levels of pro-in ammatory cytokines, such as interleukin 1 (IL-1), tumor necrosis factor α (TNF-α), and mainly interleukin 6 (IL-6) induces production of CRP in the liver 18,19 . As we all known, apoA-I has been supposed to be related with tumor necrosis factor-α (TNF-α) 20 .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Moreover, several epidemiological studies clearly established that smoking increases the risk of developing CC, by helping human papillomavirus survival and leading to the development of invasive lesions several years after initial infection. [26][27][28] Tumor size is a well-known negative prognostic factor in CC. 29,30 Here, it was found to be related to RFS even more than the FIGO 2009 classification.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was found to be negatively related to OS, supporting findings of previous studies that demonstrated cigarette smoking decreases survival in LACC patients treated by RT or CCRT. 24,25 Moreover, several epidemiological studies clearly established that smoking increases the risk of developing CC, by helping human papillomavirus survival and leading to the development of invasive lesions several years after initial infection 26‐28 . Tumor size is a well‐known negative prognostic factor in CC 29,30 .…”
Section: Discussionmentioning
confidence: 99%